Workplace violence against medical staff - CURTEANU, Maria (One Health & Risk Management, 2021)
Introduction. Violence, whether domestic or at work, has always been a problem of human interaction with repercussions on how health professionals manage to care for people. If a few decades ago, violence in hospitals seemed to affect medical staff less often and respect for medical staff seemed self-evident, then aggression is often more encountered now and examples from the media are becoming more common. Doctors are those who save lives, only that they might become a subject to an increased risk. The capacity and effectiveness of the work of medical staff depend, largely, on their working conditions and risk factors. The activity of medical workers requires intellectual, neuro-emotional efforts of the analyser system, physical efforts with dynamic and static muscular overloads, vicious work positions.Material and methods. The purpose of this research is to study the phenomenon of violence and identify the workplace risk factors on the health of medical staff. This descriptive study used and analysed the data retrieved from the international and national databases.Results. Verbal and physical violence against healthcare workers have reached considerable levels worldwide and the World Medical Association has most recently defined violence against health personnel “an international emergency that undermines the very foundations of health systems and impacts critically on patient's health”. The consequences of violence against healthcare workers can be very serious: deaths or life-threatening injuries, reduced work interest, job dissatisfaction, decreased retention, more sick leave days, impaired work functioning, depression, post-traumatic stress disorder, decline of ethical values, and increased practice of defensive medicine. Workplace violence is associated directly with higher incidence of burnout syndrome, lower patient safety, and more adverse events. A study conducted in Romania by CMMB in 2015 showed the magnitude of the phenomenon as follows: 85% of doctors said they had experienced verbal aggression and 10.2% physical aggression. Most doctors who have been victims of violence at workplace have not filed a complaint against aggressive patients or relatives who physically or verbally assaulted them. Violent manifestations often affect patients as well. The threat of using force or even brutality to obtain a privileged and unnecessary treatment deprives other patients of vital resources. There is a double pressure on doctors viz. the patients, who want the best possible treatment, without thinking about the fact that there may be more serious cases, which require more quick attention, and the public system, which requires resource planning so that the right to treatment of other patients is also protected. The most important element of reducing violence is the ability to communicate, however verbal aggressions are more common, since more than half of all cases are related to these situations. In this context, it is necessary to introduce communication courses for future doctors or nurses and education campaigns for the overall population, as well as legislation that provides harsher punishments for those who commit violence against healthcare workers engaged in public health service.Conclusions. This study must be developed in order to achieve an overview regarding the problem of workplace violence against healthcare workers from the Republic of Moldova.